1996
DOI: 10.1111/j.1469-8137.1996.tb01846.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating microclimatic influences on ozone injury in clover (Trifolium subterraneum) using artificial neural networks

Abstract: SUMMARYMicroclimatic factors interact during ozone episodes to influence the sensitivity of plants to ozone and thus arc likely to modify the amount of injury development. This paper investigates these interactions in an ozone-sensitive cultivar of clover {Trifolium subterraneum cv. Geraldton). Experiments were conducted using a glasshouse-based closed-chamber exposure system in which the plants were exposed for 7 h to either chareoal-filtered air {CF) or CF plus ozone at concentrations ranging from 40 to 160 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…First, expression of symptoms is affected by environment, especially soil water deficit, vapour pressure deficit, light, temperature (Sand, 1960 ;Shinohara et al, 1973 ;Dunning & Heck, 1977 ;Keitel & Erhardt, 1987 ;Showman, 1991) and possibly u.v.-B radiation (Thalmair et al, 1995). In a recent study, Balls, Palmer-Brown & Sanders (1996) used artificial neural networks to examine the effects of microclimate on the threshold ozone dose for visible injury in Trifolium subterraneum. The analysis indicated that VPD and PAR had a stronger influence on the response to ozone than did temperature, and that microclimate had a greater influence on the extent of ozone injury than on the threshold for injury.…”
Section: Visible Symptomsmentioning
confidence: 99%
“…First, expression of symptoms is affected by environment, especially soil water deficit, vapour pressure deficit, light, temperature (Sand, 1960 ;Shinohara et al, 1973 ;Dunning & Heck, 1977 ;Keitel & Erhardt, 1987 ;Showman, 1991) and possibly u.v.-B radiation (Thalmair et al, 1995). In a recent study, Balls, Palmer-Brown & Sanders (1996) used artificial neural networks to examine the effects of microclimate on the threshold ozone dose for visible injury in Trifolium subterraneum. The analysis indicated that VPD and PAR had a stronger influence on the response to ozone than did temperature, and that microclimate had a greater influence on the extent of ozone injury than on the threshold for injury.…”
Section: Visible Symptomsmentioning
confidence: 99%
“…The use of artificial neural network (ANN) models to analyse the interactions between microclimate, AOT40 and injury was described in detail by Balls et al (1996). A number of ANN models were created using a back propagation algorithm within the Neuroshell 2 package (Ward Systems Group, Frederick, MD, USA).…”
Section: Artificial Neural Network Model Analysismentioning
confidence: 99%
“…A similar effect of increased air vapour pressure deficit (VPD) has long been recognized (MacDowall et al, 1964). In order to analyse the role of these modifying factors and their relative importance, Artificial Neural Networks (ANNs) have been used (Balls et al, 1995 ;Balls et al, 1996), and their use could be extended to include plant-specific factors. It was confirmed that VPD is one of the most important factors determining the occurrence of short-term visible injury under well watered conditions (Balls et al, 1996).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one type of input vectors was formed (with dimension (12x1)). (c) Stage 3: Using the two versions of "Stepwise" sensitivity analysis method [37,38,39] the number and the combination of seismic input parameters which lead to the optimum ANNs' predictions for the seismic damage state of r/c buildings was investigated. Thus, in this stage input vectors with dimension between (5x1) and (12x1) were formed.…”
Section: Investigation Of Optimum Performance Of Anns With One Hiddenmentioning
confidence: 99%